2020
DOI: 10.3389/fmats.2020.578411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Toxicity of Ionic Liquids on Shewanella sp. for Designing Sustainable Bioprocesses

Abstract: Ionic liquids (ILs) are widely used as reaction and separation media in many technologies due to their unique and advantageous physicochemical properties. Thus, further studies approaching the study of the toxicity of these materials are required. Moreover, they are utilized in devices in which microorganisms such as Shewanella sp. act as biocatalysts. Thus, in this work, the toxicity of 69 ILs on the marine bacterium Shewanella sp. was tested. Specifically, the ILs analyzed were based on the cations imidazoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…It is also important to remark the high toxicity observed for [Bmim+ ] [BF 4 − ] compared to [BDImim + ] [BF 4 − ].The inclusion of the methyl substituent in the R2 position of the imidazolium ring could reduce the acidic proton in 2, so lowering the toxicity of the IL. This effect was also recently observed for Shewanella[89].…”
supporting
confidence: 84%
“…It is also important to remark the high toxicity observed for [Bmim+ ] [BF 4 − ] compared to [BDImim + ] [BF 4 − ].The inclusion of the methyl substituent in the R2 position of the imidazolium ring could reduce the acidic proton in 2, so lowering the toxicity of the IL. This effect was also recently observed for Shewanella[89].…”
supporting
confidence: 84%
“…microorganism was largely incompatible with ILs with long alkyl chains that contained phosphonium-based cations. 78 Although it was previously assumed that the cation was the primary cause of toxicity, however, the importance of the anion should not be overlooked. Cho et al (2008) reported the toxicity of [Bmim]-based cation with different anions such as Br − , Cl − , [BF 4 ] − , [PF 6 ] − , [CF 3 SO 3 ] − , [C 8 H 17 SO 4 ] − and [SbF 6 ] − on Selenastrum capricornutum .…”
Section: Resultsmentioning
confidence: 99%
“…microorganism was largely incompatible with ILs with long alkyl chains that contained phosphonium-based cations. 78 Although it was previously assumed that the cation was the primary cause of toxicity, however, the importance of the anion should not be overlooked. ] − , which could be due to their ability to undergo hydrolysis in water.…”
Section: Toxicity Of Ionic Liquidsmentioning
confidence: 99%
“…To that end, past studies showed that reducing hydrophobicity of alkyl chains was key to lowering IL toxicity. [33][34][35][36][37] In exploring this structure-activity relationship, Coleman and Gathergood proposed that adding polar functional groups, especially protic moieties, to alkyl side chains significantly decreases the likelihood of IL toxicity. 34 Despite the cation's primary role in narcosis, Cho et al and Santos et al showed that some anions, such as fluorinated ones, drive toxicity in imidazolium and cholinium-based ILs, which are generally regarded as safe.…”
Section: Introductionmentioning
confidence: 99%